POTRET KEHIDUPAN BUNDO KANDUANG DI MINANGKABAU DALAM NOVEL LIMPAPEH KARYA A.R. RIZAL - Putri, Revitra Yulia Eka; Juita, Novia; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2018)
The purposes of this study to describe the description of the life of bundo kanduang in Minangkabau in Limpapeh's novel by A.R. Rizal is seen from the properties, duties and responsibilities, as well as the role of the bundo kanduang in Limpapeh's novel by A.R. Rizal. This research type is qualitative research by using descriptive method. Based on the results of research and discussion can be concluded that a bundo kanduang must be a role model in life so it must have some properties, such as true, clever, articulate, and has the nature of shame. Furthermore, in the life of a bundo kanduang must perform duties and obligations, such as manuruik alua nan luruih, manampuah nan pasa, mamaliharo harato jo pusako, and mamaliharo child and nephew. Then in his life, a bundo kanduang has two roles: the role of domestic (in the family) and the public role (according to the profession and position).Keywords: bundo kanduang, Minangkabau, Limpapeh